Effect of microstructure on slip-induced crack initiation and early propagation of martensitic steel during high cycle fatigue. (February 2023) - Dai, Yajun; Wang, Shijian; He, Qiyuan; Liu, Chang; Wang, Xiangyu; Li, Xue; Li, Lang; Liu, Yongjie; He, Chao; Wang, Qingyuan
Highlight: Slip bands initiated inside martensitic laths, are oriented parallel to the lath. Internal slip bands of the martensitic laths cause cracks to initiate. Crack are more likely to propagation along the martensitic laths. The complex structure of martensite has a greater resistance to small crack growth. Abstract: Martensitic steel presents high fatigue crack resistance due to its complex and hierarchical microstructure, but its mechanisms are unclear. This work experimentally investigated effect of the lath and the prior austenitic grain (PAGs) on crack initiation and the early propagation behavior in high cycle fatigue. It is found that micro cracks initiated from the slip bands in the interior of thin monocrystalline laths, in which the dislocation intensity zones deflected the crack path. Subsequently, the micro cracks coalesced through the lath boundaries, and resulted in an intermittent and staggered appearance of crack path in the PAGs. Finally, the crack propagation across the boundaries of the primary PAG are extremely slow and presents significant zigzag manners due to the misorientation of the laths in neighboring PAGs. The above observations demonstrate that the crack initiation and early propagation are significantly hindered by the multi-scaled microstructure of the martensitic steel.